The Role of Fiscal Incentives in Enhancing the Plastic Recycling Industry: Addressing Waste Generation in Indonesia - Kayla Aurelianisa; Maria R.U.D. Tambunan (School of Postgraduate Studies, Diponegoro Univer, 2025)
Efforts to address the issue of waste generation in Indonesia are being realized through the application of the circular economy concept in the plastic recycling industry. However, the growth of this industry faces several challenges, such as limited raw material availability and inadequate recycling technology. Therefore, government support in the form of fiscal incentives has become an urgent necessity. This study aims to analyze the urgency of providing fiscal incentives, the challenges in formulating consumption tax incentive policies, and efforts to optimize the utilization of these incentives by plastic recycling industry players. Using a qualitative approach and descriptive research method, data were collected through literature reviews and field studies. The research findings indicate that adequate raw material availability and technology are critical challenges, aside from the need for additional fiscal incentives to overcome these limitations. However, there are also challenges in policy formulation, particularly regarding the alignment of proposed policies with existing regulations. Although fiscal incentives, such as cost reductions for recycling machinery investment, are already available, their utilization remains suboptimal due to insufficient socialization. To address this issue, coordination among policymakers from policy formulation to evaluation stages is necessary, as well as increased outreach efforts regarding the use of fiscal incentives through collaboration with relevant field stakeholders.